2016
DOI: 10.1097/md.0000000000003836
|View full text |Cite|
|
Sign up to set email alerts
|

The biophysical characterization of the first SCN5A mutation R1512W identified in Chinese sudden unexplained nocturnal death syndrome

Abstract: Increasing evidence observed in clinical phenotypes show that abrupt breathing disorders during sleep may play an important role in the pathogenesis of sudden unexplained nocturnal death syndrome (SUNDS). The reported Brugada syndrome causing mutation R1512W in cardiac sodium channel α subunit encoded gene SCN5A, without obvious loss of function of cardiac sodium channel in previous in vitro study, was identified as the first genetic cause of Chinese SUNDS by us. The R1512W carrier was a 38-year-old male SUNDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In this study, we identified, once again, that breathing‐disorder–related acidosis plays a crucial role for VCL‐D841H in aggravating SCN5A loss of function. All these findings strongly implicate the possible important contribution of sleep respiratory disorders in the occurrence of SUNDS …”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In this study, we identified, once again, that breathing‐disorder–related acidosis plays a crucial role for VCL‐D841H in aggravating SCN5A loss of function. All these findings strongly implicate the possible important contribution of sleep respiratory disorders in the occurrence of SUNDS …”
Section: Discussionmentioning
confidence: 57%
“…Plant et al previously reported that sleep respiratory abnormality‐associated intracellular acidosis significantly increased the late I Na caused by the sudden infant death syndrome susceptibility SCN5A common variant, S1103Y, in blacks. Recently, the SCN5A mutation, R1512W, found in a Chinese SUNDS victim with sudden nocturnal tachypnea before death was identified to show obvious SCN5A loss of function only under acidosis conditions . In this study, we identified, once again, that breathing‐disorder–related acidosis plays a crucial role for VCL‐D841H in aggravating SCN5A loss of function.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…37 Using the whole-cell patch clamp method, we proved that intracellular and extracellular acidosis significantly decreases wild or mutant sodium currents in vitro co-expression systems. 38,39…”
Section: Potassium Deficiencymentioning
confidence: 99%